Resource utilisation and social behaviour of the Cape grey mongoose, Galerella pulverulenta - Mudge, Tanya Natasha (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1999.